Presença indígena em unidades de conservação - Abi-Eçab, Pedro (2008)
This paper aims to analyze the issue of indigenous people presence in conservation units, from the perspective of Environmental Law. The theme is analyzed with focus on the shock between the constitutional metaindividual interests of indigenous people and of the present and future collectivity, and the ecologically balanced environment. The concepts and characteristics of the man s fundamental rights are studied, as well as the principle of historicity characterizing them and, consequently, the socalled generations of rights, passing through the rupture between public and private, then coming to the metaindividual rights, which are composed of two categories: fundamental rights and diffuse rights. Due to the fundamental rights diversity and to the contemporaneous society complexity, the shock between fundamental rights is becoming commonplace, with resolution becoming necessary through a weighting system. Conflicting interests are analyzed, studying the right to the environment and its principles, as well as the indigenous people right to the land and the indigenous land legal system. The legal system of conservation units is shown, showing the preservationism vs. conservationism conflict of visions. In addressing the presence of indigenous people in conservation units, themes such as the myth of the bon sauvage and of the untouched nature are discussed, as well as the ethnical transfiguration of indigenous people, and then two hypotheses of the indigenous people presence: the occupation of conservation units by indigenous people and the creation of conservation units superposing indigenous land. The paper proposes the review of certain institutes such as the indigenous land intangibility, as well as the acknowledgment of the supremacy of the fundamental right to a healthy and ecologically balanced environment, coming to the conclusion that the first one, i.e. the intangibility, does not prevail over the second. On the other side, through conflict resolution mechanisms applying weighting rules, it is verified that the problem does not bear an exclusive solution, but rather differentiated solutions according to the case, thus excluding all-or-nothing solutions